Comparative Investigation on the Properties and Molecular Mechanisms of Natural Phenolic Compounds and Rubber Polymers to Inhibit Oxidative Aging of Asphalt Binders - Fenghua Yang; Zhuang Hu; Hongyi Xi (Advances in Materials Science and Engineering)
Using bio-based antioxidants and industrial wastes to inhibit asphalt aging is a sustainable practice in the pavement industry. To investigate the inhibitory effects and potential mechanisms of phenolic compounds and crumb tire rubber on the aging deterioration of asphalt binders, the aging characteristics of base asphalt, catechin modified asphalt, and crumb rubber modified asphalt were evaluated using Fourier transform infrared spectroscopy and reactive molecular dynamics simulations. The results showed that both catechins and crumb rubber exerted resistance to asphalt aging and that the former performed better. Specifically, catechins block asphalt aging at the chemical level by providing active H atoms to react with O2 and free radicals, thus preventing them from oxidizing asphalt molecules. In contrast, crumb rubber exerts its antiaging properties mainly in physical aspects, firstly by limiting the movement of asphalt molecules to reduce the contact and reaction of asphalt with O2 and secondly by counteracting the aging-induced asphalt hardening through its own degradation, thus partially restoring the mechanical properties of aged asphalt. This study provides molecular insight into the antiaging mechanisms of natural phenolic compounds and rubber polymers and is expected to provide theoretical guidance for the development of targeted antiaging technologies for asphalt binders.